Cocaine Self-administration Regulates Transcription of Opioid Peptide Precursors and Opioid Receptors in Rat Caudate Putamen and Prefrontal Cortex. (1st September 2020) - Sun, Haiguo; Luessen, Deborah J.; Kind, Kathleen O.; Zhang, Ke; Chen, Rong
Highlights: Cocaine self-administration produces a broad impact on gene expression of opioid receptors and endogenous peptide precursors. Cocaine self-administration produces greater effects on transcription of Oprm and Oprd in both the CPu and PFC than that of Oprk. Cocaine self-administration induces opposing effects on transcription of Penk/Pdyn and Pomc in the CPu. The Pomc transcription in the CPu is most susceptible to the effect of cocaine self-administration. Abstract: The brain opioid system plays an important role in cocaine reward. Altered signaling in the opioid system by chronic cocaine exposure contributes to cocaine-seeking and taking behavior. The current study investigated concurrent changes in the gene expression of multiple components in rat brain opioid system following cocaine self-administration. Animals were limited to 40 infusions (1.5 mg/kg/infusion) within 6 h per day for five consecutive days. We then examined the mRNA levels of opioid receptors including mu ( Oprm ), delta ( Oprd ), and kappa ( Oprk ), and their endogenous opioid peptide precursors including proopiomelanocortin ( Pomc ), proenkephalin ( Penk ), prodynorphin ( Pdyn ) in the dorsal striatum (CPu) and the prefrontal cortex (PFC) 18 h after the last cocaine infusion. We found that cocaine self-administration significantly increased the mRNA levels of Oprm and Oprd in both the CPu and PFC, but had no effect on Oprk mRNA levels in either brain region. Moreover, cocaine had a greater influence on the mRNA levels of opioid peptide precursors in rat CPu than in the PFC. In the CPu, cocaine self-administration significantly increased the mRNA levels of Penk and Pdyn and abolished the mRNA levels of Pomc . In the PFC, cocaine self-administration only increased Pdyn mRNA levels without changing the mRNA levels of Pomc and Penk . These data suggest that cocaine self-administration influences the expression of multiple genes in the brain opioid system, and the concurrent changes in these targets may underlie cocaine-induced reward and habitual drug-seeking behavior.